2012
DOI: 10.1111/j.1741-2358.2010.00423.x
|View full text |Cite
|
Sign up to set email alerts
|

Geriatric dentistry – meet the need

Abstract: Geriatric dentistry -meet the needGeriatric dentistry or gerodontics is the delivery of dental care to older adults involving the diagnosis, prevention, and treatment of problems associated with normal ageing and age-related diseases as part of an inter-disciplinary team with other health care professionals. Geriatric health is an ignored and underexplored area worldwide. Oral health reflects overall well being for the elderly population. Conversely, elderly patients are more predisposed to oral conditions due… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
44
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 17 publications
(18 reference statements)
2
44
0
1
Order By: Relevance
“…This perception is also reflected in dentists' general reluctance to treat (and low interest in treating) older people residing in long-term care facilities [40,47]. Dental professionals regard providing such a service as a minimal financial gain and this lack of competence, confidence and interest must be addressed by adequate training in the area of gerodontology so that the older population in need can be served [48]. Undergraduate education is the seedbed for conscientious professionals [49], and it is therefore important to place S i n g a p o r e D e n t a l J o u r n a l 3 5 ( 2 0 1 4 ) 3 -8 appropriate emphasis on oral health care for older patients in the undergraduate curriculum [50][51][52][53].…”
Section: Shaping a Gerodontologically Capable And Responsive Workforcementioning
confidence: 98%
“…This perception is also reflected in dentists' general reluctance to treat (and low interest in treating) older people residing in long-term care facilities [40,47]. Dental professionals regard providing such a service as a minimal financial gain and this lack of competence, confidence and interest must be addressed by adequate training in the area of gerodontology so that the older population in need can be served [48]. Undergraduate education is the seedbed for conscientious professionals [49], and it is therefore important to place S i n g a p o r e D e n t a l J o u r n a l 3 5 ( 2 0 1 4 ) 3 -8 appropriate emphasis on oral health care for older patients in the undergraduate curriculum [50][51][52][53].…”
Section: Shaping a Gerodontologically Capable And Responsive Workforcementioning
confidence: 98%
“…Some are unable to live independently as a result of their age and/or disease, and require institutionalization in long-term care facilities 1,2 . Multiple systemic diseases and their treatments can impair oral health and, consequently, the quality of life of an elderly person [3][4][5] . Th e most common oral diseases among the elderly are dental caries, tooth loss, gingivitis, periodontitis, decreased salivary fl ow, candidiasis, and oral cancer 2,6 .…”
Section: Introductionmentioning
confidence: 99%
“…Some people may not consume some foods that are good sources of dietary fiber due to problems with their teeth or dentures. 10 Makwana et al 11 evaluated the nutritional status in dentulous and edentulous denture-wearing elderly patients and found that risk of malnutrition was eight times higher in edentulous as compared with dentulous subjects. To sum up, there are profound and complex links between nutrition and oral health .…”
Section: Discussionmentioning
confidence: 99%